Gender Mainstreaming through Livestock Entrepreneurship - Jadoun, Y.S. (Indian Journal of Extension Education, 2019)
Women share of workforce in agriculture, livestock, forestry and fishery is more than 50 per cent in all states. Despite considerable involvement and contribution of women in the society, gender inequalities exist in access to technologies, credit, information, inputs and services including land and livestock and their contribution is rarely acknowledged. Participation of women in economic activities is now emerging as a universal phenomenon. Social and economic empowerment through entrepreneurial skill of women is the key factor for overall development of any country. Challenges usually faced by women entrepreneurs in India include low literacy rate (60% of women are still illiterate), visualized role of women as confined to household activities only, lack of access to resources, lack of motivation, lack of support from family members, lack of suitable infrastructure, lack of marketing facilities and lack of proper storage facilities in rural areas. Besides these, they are also plagued by low risk bearing ability, lack of information regarding new technologies, lack of training, lack of finance and other social and cultural constraints. The present paper is an attempt to highlight the interwoven nexus of gender mainstreaming, women empowerment, livestock and rural women. The paper also suggests some of the approaches to develop women entrepreneurship in livestock sector.
Keywords: Aquaculture; Dairy; Entrepreneurship; Gender; Livestock; Poultry